Environmental magnetic and geochemical characteristics of Chennai coastal sediments, Bay of Bengal, India - Venkatachalapathy, R.; Veerasingam, S.; Basavaiah, N.; Ramkumar, T.; Deenadayalan, K. (My University, 2011)
In this study, environmental magnetic, heavy metal and statistical analyses were conducted on 21 surface sediments collected from Chennai coast, India, to examine the feasibility of heavy metal pollution using magnetic susceptibility. The Chennai coastal sediment samples are dominated by ferrimagnetic minerals corresponding to magnetite-like minerals. The percentage of frequency dependent magnetic susceptibility reflects the presence of super-paramagnetic/single domain magnetic minerals in Chennai harbour, Cooum and Adayar rivers sediments. High pollution load index in sample E1, E2, CH7, C11, C12 and A16 is mainly due to anthropogenic activities such as, harbour activities, Cooum and Adayar rivers input and industrial effluent. Factor analysis shows that the magnetic concentration dependent parameters (χ, χ ARM and SIRM) covary with the heavy metal concentrations, suggesting that the input of magnetic minerals and heavy metals in Chennai coastal sediments are derived from the same anthropogenic sources. Strong correlation obtained between pollution load index (PLI) and concentration dependent parameters (χ, χ ARM and SIRM) for the polluted samples with magnetic susceptibility excess of 50×10 − 8 m3kg − 1. Significant correlations between heavy metals and magnetic susceptibility point out the potential of magnetic screening/monitoring for simple and rapid proxy indicator of heavy metal pollution in marine sediments.
Keywords: Environmental magnetism; Heavy metals; Pollution load index; Marine sediments; Multivariate statistical analysis